2020
DOI: 10.1097/ijg.0000000000001560
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Hypotony and Annular Ciliochoroidal Detachment After Microhook Ab Interno Trabeculotomy

Abstract: Précis: Creation of a cyclodialysis cleft can be a mechanism of ciliochoroidal detachment (CCD) and associated persistent hypotony after microhook ab interno trabeculotomy (μLOT). Aims: To report persistent hypotony after μLOT, a minimally invasive glaucoma surgery (MIGS). Subjects and Methods: This observational case series included 4 consecutive cases (3 men, 1 woman; mean age, 48.8±15.1 y) of persistent h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Sato et al reported that CCDs detected by AS-OCT developed in 21 of 44 eyes (48%) within 7 days after 360-degree suture LOT; the CCDs resolved in 19 eyes within 1 month and in two eyes by 3 months [17]. We previously reported four cases of hypotony that persisted from the early post-operative periods [18]. Thus, CCDs generally are not rare events after MIGS surgery and seem to be associated with IOP reductions immediately postoperatively [18].…”
Section: Discussionmentioning
confidence: 91%
“…Sato et al reported that CCDs detected by AS-OCT developed in 21 of 44 eyes (48%) within 7 days after 360-degree suture LOT; the CCDs resolved in 19 eyes within 1 month and in two eyes by 3 months [17]. We previously reported four cases of hypotony that persisted from the early post-operative periods [18]. Thus, CCDs generally are not rare events after MIGS surgery and seem to be associated with IOP reductions immediately postoperatively [18].…”
Section: Discussionmentioning
confidence: 91%
“…In the current case series, persistent hypotony subsequent to ciliochoroidal detachment (CCD) developed in four eyes. As discussed previously [ 40 ], increased uveoscleral outflow due to LOT [ 41 ] or the creation of a cyclodialysis cleft by traction of the pectinate ligament [ 40 ] can be a mechanism of CCD development. Akagi et al reported that a CCD detected by anterior-segment OCT developed in 14 (42%) of 33 eyes 3 days after a Trabectome procedure; the CCD persisted in four eyes (12%) at 1 month and resolved by 3 months [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another case,11 similarly reports good long-term prognosis results with direct cyclopexy surgery, following failed medical and laser treatment of cyclodialysis cleft secondary to cataract extraction, combined with an AIT with Trabectome. A recent case series12 documented treatment after sulphur hexafluoride gas injection was efficacious.…”
Section: Discussionmentioning
confidence: 99%